Analysing competitiveness and trade performance: evidence from Indian textile industry and its select competitors. Issue 4 (1st October 2020) - Gautam, Shweta; Lal, Madan
Abstract: The present study investigates the trade performance and competitiveness of textile industry of India and its competitors namely China and Vietnam by using revealed comparative advantage developed by Balassa, and other trade parameters given by World Bank in terms of growth, diversification and sophistication for 1988 to 2016. Data has been taken from World Integrated Trade Solution (WITS) based on harmonised system (HS-2) including 11 products ranging from HS-50 to HS-60. Results indicate that India has attained comparative advantage from 7 products to only 8 Products While Vietnam has shown drastic improvement in textile products and has achieved comparative advantage from 2 products to 7 products during 2000 to 2016. Moreover, China has improved its comparative advantage from 9 products to all products. The study concluded that there are immense opportunities for Indian textile industry in world market as most of the products have shown positive growth of export.